Developing a delay risk model for toll road construction project: A conceptual framework - Pratama, G A; Latief, Y (Applied Engineering and Technology, 2022)
In the realization of the medium-term development plan in 2014-2019 (RPJMN), toll road construction development was only reached 51 percent. construction projects had complex and dynamic nature, which caused delays, construction risk assessment that considers risk as a system was done before, for example, using techniques such as SD, Fuzzy DEMATEL, STEEP-SD, DEMATEL-ANP, and SD-DEMATEL, but the technique still has some shortcomings. in indonesia, research related to this matter is still rarely done, to address this concern, we propose a conceptual framework that can be used to develop a delay risk model for toll road construction project especially in indonesia. for this purpose, we introduce the system dynamic-fuzzy dematel-anp (sd-fdanp) method. the results of the development of the sd-fdanp method can be used as a guideline that can help achieve behavioral knowledge of delays and the success of risk assessment in toll road infrastructure development projects.